Endogenous Alcohol and Auto-Brewery Syndrome Complicating Liver Transplantation: A Case Report and Literature Review - Jack C. Drda; Jill P. Smith (Livers)
Introduction: We describe the first reported case of auto-brewery syndrome complicating liver transplantation, wherein a patient was temporarily removed from a liver transplant list not due to ethanol consumption but rather spontaneous ethanolic fermentation within the gastrointestinal tract. Auto-brewery syndrome (ABS) is a rare metabolic condition where gastrointestinal microbiota dysbiosis leads to spontaneous microbial ethanolic fermentation under anaerobic, high carbohydrate conditions. Because no alcohol is directly consumed by the patient, this alcohol is often referred to as “endogenous”. Methods: We present a case where a patient awaiting orthotopic liver transplantation was removed from the transplant list due to significantly elevated blood alcohol levels. However, an upper endoscopy revealed Candida esophagitis, and the diagnosis of ABS was made. Results: With antifungal fluconazole treatment, the patient’s blood alcohol biomarkers decreased, and the patient underwent a successful liver transplantation. Discerning between patient exogenous alcohol consumption and endogenous alcohol production with ABS remains a significant challenge for clinicians, and this knowledge could have serious implications for a patient awaiting a life-saving liver transplant. Conclusions: This case highlights the importance of listening to the patient and carefully assessing potential liver transplant recipients who consistently deny alcohol consumption, specifically for gut dysbiosis and ABS.